Critical Geopolitics and Post-Critical Shift in Geopolitical Research Paradigm - I. Yu. Okunev (Сравнительная политика, 2015)
Th e article presents a review of the new geopolitics approach that developed in the West in the last two decades — the critical geopolitics. Th e article analyzes its methodological and thematic innovations, the contradictions between classical and critical geopolitics, and regards possible future cooperation of the opposing approaches as post-critical shift in geopolitics research paradigm.